Efeito antimicrobiano de múltiplas sessões de tereapia fotodinâmica sobre biofilmes de Candida spp. formados in vitro - Freitas, Lírian Silva de Figueiredo [UNESP] (2015)
Several in vitro studies have demonstrated the antimicrobial effects of photodynamic therapy (PDT) against yeast of the genus Candida, representing an alternative or coadjuvant tool for the treatment of denture stomatitis. Therefore, the objective of this study was to evaluate the antifungal effect of multiple PDT sessions on Candida biofilms formed on the surface of acrylic resin. For this purpose, monotypic biofilms of C. albicans, C. tropicalis and C. glabrata were grown for 5 days on test specimens consisting of thermally activated acrylic resin. Next, the biofilms formed were submitted to five sessions of PDT at intervals of 24 hours. Two modalities of PDT were evaluated: a gallium-aluminum-arsenide laser combined with methylene blue as photosensitizer, and a green light-emitting diode (LED) and erythrosine as photosensitizer. The control groups were only treated with saline. After each application of PDT, the biofilms adhered to the test specimens were submitted to ultrasonic homogenization and the dispersed cells were seeded onto Sabouraud dextrose agar (37 oC, 48 h) for determination of colony-forming units (CFU/test specimen). Analysis of variance (ANOVA) and the Tukey test were used for analysis of the results, adopting a level of significance of 5%. For all microorganisms, the results of CFU(log) reduction were compared to controls of the first, second, third, fourth and fifth application of the laser and LED. For C. glabrata, the reductions in each application were, respectively, 3.22 and 4.83, 1.49 and 2.21, 1.6 and 2.05, 1.53 and 5.09, and 2.75 and 3.03. Reductions of 0.12 and 0.36, 0.54 and 0.93, 0.15 and 0.06, 0.96 and 0.75, and 0.89 and 1.82 were observed for C. albicans. Candida tropicalis showed the following reductions: 0.16 and 0.14, 1.52 and 2.84, 1.86 and 2.1, 1.81 and 2.39, and 0.86 and 1.36. In conclusion, laser- and LED-mediated PDT were effective in reducing...